Effects of Blindfold on Leadership in Pediatric Resuscitation Simulation: A Randomized Trial - Buyck, Michael; Manzano, Sergio; Haddad, Kevin; Moncousin, Anne-Catherine; Galetto-Lacour, Annick; Blondon, Katherine; Karam, Oliver (Frontiers in Pediatrics, 2019)
Background: Pediatric resuscitations are rare events. Simulation-based training improves clinical and non-clinical skills, as well as survival rate. We assessed the effectiveness of using blindfolds to further improve leadership skills in pediatric simulation-based training. Methods: Twelve teams, each composed of 1 pediatric emergency fellow, 1 pediatric resident and 2 pediatric emergency nurses, were randomly assigned to the blindfold group (BG) or to the control group (CG). All groups participated in one session of five simulation-based resuscitation scenarios. The intervention was using a blindfold for the BG leader for the scenarios B, C, and D. Three evaluators, who were blinded to the allocation, assessed leadership skills on the first and last video-recorded scenarios (A and E). Questionnaires assessed self-reported changes in stress and satisfaction about skills after the first and the last scenarios. Results: Improvement in leadership skills doubled in the BG compared with the CG (11.4% versus 5.4%, p=0.04), whereas there was no increase in stress or decrease in satisfaction. Conclusion: Blindfold could be an efficient method for leadership training during pediatric resuscitation simulated scenarios. Future studies should further assess its effect at a follow-up and on clinical outcomes after pediatric resuscitation.